Clinical features and resolution of food protein–induced enterocolitis syndrome: 10-year experience - Caubet, Jean Christoph; Ford, Lara Simone; Sickles, Laura; Järvinen, Kirsi M.; Sicherer, Scott H.; Sampson, Hugh A.; Nowak-Węgrzyn, Anna (Journal of allergy and clinical immunology, 2014)
Food protein–induced enterocolitis syndrome (FPIES) is a non–IgE-mediated food allergy. FPIES diagnosis is frequently delayed because of the absence of classic allergic symptoms and lack of biomarkers. We sought to characterize the clinical features and resolution of FPIES in patients evaluated in our practice. Subjects 6 months to 45 years of age with FPIES were prospectively recruited for oral food challenges (OFCs). Medical records were searched to identify the subjects who did not participate in OFCs. Among 160 subjects, 54% were male; median age at diagnosis was 15 months. We performed 180 OFCs to 15 foods in 82 subjects; 30% of the study population had FPIES confirmed based on OFC results. The most common foods were cow's milk (44%), soy (41%), rice (22.5%), and oat (16%). The majority (65%) reacted to 1 food, 26% reacted to 2 foods, and 9% reacted to 3 or more foods. The majority were atopic, and 39% had IgE sensitization to another food. Thirty-nine (24%) subjects had positive specific IgE levels to the food inducing FPIES. Among children with specific IgE to cow's milk, 41% changed from a milk FPIES to an IgE-mediated phenotype over time. The median age when tolerance was established was 4.7 years for rice, 4 years for oat, and 6.7 years for soy. Median age when milk tolerance was established for subjects with undetectable milk-specific IgE levels was 5.1 years, whereas none of the subjects with detectable milk-specific IgE became tolerant to milk during the study (P = .003). FPIES typically resolves by age 5 years. Milk FPIES, especially with detectable food-specific IgE, can have a protracted course and eventually transition to acute reactions.